The effects of in ovo injected with sodium borate on hatching performance and small intestine morphology in broiler chicks - Bozkurt Mehmet Fatih; Peşmen Günnur (Open Chemistry, 2023)
The objective of this study was to investigate the effects of in ovo injection of sodium borate on hatching power, chick weight, chick length in fertile broiler eggs. A total of 256 fertile broiler eggs were incubated in the study. On Day 18 of incubation, two groups were injected with 0.1 mL of 0.5 mg and 1 mg of sodium borate dissolved in saline, and two groups were used as sham control (injected with 0.1 mL of saline) and uninjected control. Hatching power was apparently increased (P ≤ 0.05) by in ovo injection of sodium borate (0.5 mg) rather than control groups and sodium borate (1 mg) group. While there was no significant difference between the groups in terms of chick weights, a significant difference was found between group B and other experimental groups in terms of chick length (P < 0.05). In ovo sodium borate injection (0.5 mg) had a positive effect on villus length, crypt width, villus absorption surface (HASA), and the number of proliferating cell nuclear antigen positive crypt cells.